SCREENING OF POST PARTUM DEPRESSION ON THE SEVENTH DAY PUERPERIUM - Wahyu Desiana; Tarsikah Tarsikah (Indonesian Midwifery and Health Sciences Journal, 2021)
Abstract Background: Postpartum depression is a psychological disorder during the postpartum period which is more dangerous than the baby blues. Postpartum depression can have a serious impact on the development of the baby as well as the social life of the mother. To anticipate the incidence of postpartum depression, it is necessary to have early detection. The purpose of this study was to describe the results of the seventh day postpartum depression screening at PMB S Malang City. Methods: The design of this research is descriptive quantitative with a population of 72 postpartum mothers, the number of samples is 57 people who are taken at simple random. Research instrument: EPDS questionnaire. Results: The results showed that postpartum mothers experienced postpartum depression in as many as 22.8%. Postpartum mothers who have an EPDS score 10 are mothers with the age group > 35 years, working mothers, high school education, nuclear family type, and the number of children 2 - 3 people. Conclusion: Even in small amounts, postpartum depression can have a negative impact on maternal mental health and child development in the future, so early detection efforts need to be cultivated.